Did Becky really need to apologise? Intercultural evaluations of politeness. (8th March 2018) - Okano, Emi; Brown, Lucien
Abstract : This study analyses a public apology made in 2016 by Becky, an Anglo-Japanese tarento 'celebrity', for her romantic involvement with a married man, musician Enon Kawatani. Adopting an integrative pragmatics perspective, we analyse the pragmatic acts Becky used to perform her apology, including culture-specific nonverbal behaviours indexing deference. We then look at how the apology was dynamically evaluated in naturally occurring discourse in Japanese and British Computer Mediated Communication (CMC). The analysis shows that culture-specific moral orders rendered Becky's apology necessary in the Japanese context, but that these norms were not shared by the British audience. The Japanese and British CMC participants utilised national identity as resources for negotiating their contrasting moral orders. We show how CMC participants assign significance to the (im)politeness-related behaviour to which they were exposed and how they performed (im)politeness through threatening national identities.